2017
DOI: 10.1128/aac.02655-16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profile of Malaria Drug Resistance Markers of Plasmodium falciparum in Suriname

Abstract: In Suriname, an artesunate monotherapy therapeutic efficacy trial was recently conducted to evaluate partial artemisinin resistance emerging in Plasmodium falciparum. We genotyped the PfK13 propeller domain of P. falciparum in 40 samples as well as other mutations proposed to be associated with artemisininresistant mutants. We did not find any mutations previously associated with artemisinin resistance in Southeast Asia, but we found fixed resistance mutations for chloroquine (CQ) and sulfadoxine-pyrimethamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 23 publications
4
36
1
Order By: Relevance
“…In contrast, the K76T mutation did not appear to be associated with in vitro reduced susceptibility to piperaquine (Table 3), confirming previous results [21,38]. Previous studies found several new mutations in pfcrt associated with piperaquine reduced susceptibility, like the mutations T93S, H97Y, C101F, F145I, M343L and G353V in Cambodian parasites [22,23,[25][26][27][28][29] and C350R in isolates from French Guiana [24] and Suriname [30]. However in studies on African P. falciparum samples, there was no report of identification of these mutations [39,40].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, the K76T mutation did not appear to be associated with in vitro reduced susceptibility to piperaquine (Table 3), confirming previous results [21,38]. Previous studies found several new mutations in pfcrt associated with piperaquine reduced susceptibility, like the mutations T93S, H97Y, C101F, F145I, M343L and G353V in Cambodian parasites [22,23,[25][26][27][28][29] and C350R in isolates from French Guiana [24] and Suriname [30]. However in studies on African P. falciparum samples, there was no report of identification of these mutations [39,40].…”
Section: Discussionsupporting
confidence: 84%
“…This mutation was not found in P. falciparum positively isolates after artemether-lumefantrine treatment. A different amino acid substitution on the locus 356 (I356L) was also found in isolates from Latin America [1,30], but this mutation was absent the present 602 African isolates. However, this mutation was not observed in isolates from Suriname [30].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…An in vivo efficacy study in 2014 with artesunate further revealed that at least 17.9% of samples exhibited a parasite half-life ≥ 5 h [ 3 ]. Molecular characterizations of drug-associated markers of isolates from Suriname did not reveal noteworthy alterations in potential molecular markers in the pfATP6 [ 4 ], pfmdr1 [ 5 ] and K13 genes [ 6 ], but increased pfmdr1 copy numbers in P. falciparum isolates [ 7 ] have been observed. The possible emerging of resistance to artemisinin is further fueled with reported self-treatment and poor adherence by miners in remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…Declining e cacy of ACTs in Southeast Asia (e.g., Cambodia, Thailand) has led to heightened concern for the spread of resistant parasites to other malaria endemic countries [4,5] and the independent emergence of resistant mutants in other malaria endemic countries as was observed in Guyana [6] and Rwanda [7]. Thus, it is necessary to routinely monitor the therapeutic e cacy of ACTs.…”
Section: Introductionmentioning
confidence: 99%